The Identification Method of the Sources of Radiated Electromagnetic Disturbances on the Basis of Measurements in the Near-Field Zone - Trzcinka, Krzysztof (Journal of Automation, Mobile Robotics and Intelligent Systems, 2022)
The paper presents results of tests of a simple device, consisting in the location of a source of disturbance emission by means of measurements within the near field with manual positioning of the measuring probe. The effectiveness of the source of disturbance location was finally verified by a positive result of the radiated emission tests in the EMC laboratory using a standardised method.